2024
DOI: 10.1590/s0034-759020240101
|View full text |Cite
|
Sign up to set email alerts
|

In Search of an Integrative Framework for Female Immigrant Entrepreneurship

Victoria Barboza de Castro Cunha,
Thiago Cavalcante Nascimento,
Roberto Pessoa de Queiroz Falcão

Abstract: Female entrepreneurship (FENT) has long been presented as primarily driven by necessity, encompassing gendered social processes that push women into venturing to find independence, self-assurance, financial relief, or a more balanced lifestyle. Extant research also identified differences in motivations and barriers to female self-employment in developing versus developed countries. Thus, the article proposes an integrative framework combining Mixed Embeddedness and Institutional Theory to analyze immigrant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Por definição, autores(as) e revisores(as) apenas ficam cientes da identidade da outra parte caso o artigo seja aceito para publicação da RAE, e apenas após a sua aceitação. Exemplos de artigos recém-publicados na RAE com Avaliação por Pares Aberta (Open Peer Review) são: Cunha et al (2024), Graça e Ryngelblum (2024), Sousa e Baltazar (2024) e Toro-García et al (2024, todos publicados na edição mais recente da RAE. Além disso, não há atualmente restrições impostas pela RAE à submissão de artigos previamente disponibilizados em servidores preprints, tais como Scielo (https://preprints.scielo.org) e SSRN (https://www.ssrn.com).…”
unclassified
“…Por definição, autores(as) e revisores(as) apenas ficam cientes da identidade da outra parte caso o artigo seja aceito para publicação da RAE, e apenas após a sua aceitação. Exemplos de artigos recém-publicados na RAE com Avaliação por Pares Aberta (Open Peer Review) são: Cunha et al (2024), Graça e Ryngelblum (2024), Sousa e Baltazar (2024) e Toro-García et al (2024, todos publicados na edição mais recente da RAE. Além disso, não há atualmente restrições impostas pela RAE à submissão de artigos previamente disponibilizados em servidores preprints, tais como Scielo (https://preprints.scielo.org) e SSRN (https://www.ssrn.com).…”
unclassified
“…Notably, the identities of authors and reviewers are revealed only upon acceptance of the article for publication by RAE. Recent issues of RAE have featured articles that underwent Open Peer Review, including works by Cunha et al (2024), Graça and Ryngelblum (2024), Sousa andBaltazar (2024), andToro-García et al (2024). Additionally, RAE imposes no restrictions on the submission of articles previously shared on preprint servers such as Scielo (https:// preprints.scielo.org) and SSRN (https://www.ssrn.com).…”
mentioning
confidence: 99%